What! Cried Granny - Lum, Kate (New York Dial Books for Young Readers, 1999)
It's a boy's first sleep-over at his Granny's but what is that boy to do when he can't go to bed because something is missing? With her purse and toolbox, this Granny proves she can do anything.
Keywords: Grandmothers -- Fiction; Humorous stories; Sleep-overs -- Fiction